A Tool for Modelling of One- or Two-Step Microalgae Harvesting Processes - Martina Hladíková (AIDIC Servizi S.r.l., 2021)
Separation of microalgae from aqueous solutions still requires further optimization and knowledge. The tool for modelling of one- or two-step microalgae harvesting technology should provide a way to predict the final concentration of microalgal suspensions. The presented spreadsheet-based tool enables to determine the mass balance of the separation process and other parameters required for the equipment basic design. These parameters are the mass flow rate of individual media, an agent consumption, and the estimation of energy consumption. The tool allows a user to combine different separation processes of various separation efficiencies. A pretreatment by coagulation or flocculation before the separation process can be also included. The applicability of this approach was demonstrated on three cases.